A 3D Evaluation Method for Rail–Highway Hump Crossings. (5th December 2016) - Liu, Qingjie; Wang, Teng; Souleyrette, Reginald R.
Abstract: Rail–highway grade crossing crashes may be caused by long vehicles with low clearances becoming stranded when attempting to negotiate rail–highway crossings with steeply graded profiles—hump crossings. Although design standards have been established to encourage the construction that most vehicles are able to successfully navigate, the combination of grade profile and cross‐section interacting with unique vehicle dimensions may lead to instances where vehicles may have difficulty crossing. This article describes a three‐dimensional (3D)‐based (LiDAR) methodology to identify and evaluate the severity of hump crossings. A five‐level criterion is proposed to rate the magnitude of contact. The methodology is demonstrated by modeling seven common low‐clearance vehicle types at three types of hump crossings. Field testing indicates a good correlation between the predicted degree of vehicle‐crossing conflicts and those observed in the field. Results are applicable to operations (e.g., truck routing) or for maintenance and reconstruction programs. Future research could extend the methodology to tunnel and bridge clearances, real‐time warning systems, autonomous vehicles, or even nontransportation applications.